Алгоритм расчета количественных показателей безотказности в системах гидропневмоагрегатов на этапе их синтеза - Фатеева, Надежда Николаевна (НТУ "ХПИ", 2011)
The choice of method of calculation and determination of correlations is examined for finding of quantitative descriptions of indexes of faultlessness of hydrounits and pneumounits. The calculation of quantitative indexes of faultlessness is conducted and got algorithmfor the calculation of quantitative reliability indexes on the stage ofplanning.
Keywords: показатели надежности; свойство безотказности; экспоненциальный закон; аппаратная часть